Endoscopic Endonasal Approach to Orbital Malignant Peripheral Nerve Sheath Tumor: A Minimally Invasive Method for Rare Orbital Tumor—Case Report and Review of Literature - Praveen M. Ganigi; Arijit Chakraborty; K.M. Bopanna; Sathwik R. Shetty (Indian Journal of Neurosurgery)
Malignant peripheral nerve sheath tumors (MPNSTs) are uncommon tumors that rarely occur in the orbit. Malignant orbital tumors are always a challenge to remove completely. We present the case of a 42-year man with painful movement of the left eye and restriction of adduction of the left eye causing double vision. Magnetic resonance imaging (MRI) of the brain/orbit revealed intraconal tumor located inferomedial to the optic nerve. The imaging features were suggestive of schwannoma or cavernoma. Gross total resection of the tumor was done with an endoscopic endonasal intraconal approach. The histopathology revealed an MPNST. The patient received adjuvant radiotherapy and chemotherapy. His left eye adduction recovered completely and he had no local recurrence or systemic metastasis on follow-up evaluation.